2020
DOI: 10.3892/ijmm.2020.4722
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MKLN1‑AS aggravates hepatocellular carcinoma progression by functioning as a molecular sponge for miR‑654‑3p, thereby promoting hepatoma‑derived growth factor expression

Abstract: Long non-coding RNAs (lncRNAs) have recently gained attention due to their important roles in human cancer types, such as breast and gastric cancer. The present study measured alterations in muskelin 1 antisense RNA (MKLN1-AS) expression in hepatocellular carcinoma (Hcc) and evaluated its clinical value in patients with Hcc. Additionally, the current study investigated the effects of MKLN1-AS on the malignant features of Hcc cells. The detailed molecular mechanisms underlying the cancer-promoting activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…Among these lncRNAs, RHPN1-AS1 was reported to act as an oncogene in multiple human cancers, including nonsmall cell lung cancer [19], uveal melanoma [20], and breast cancer [21]. LINC01134 and MKLN1-AS were found to promote HCC progression or metastasis by previous studies [24][25][26][27][28], suggesting that the two lncRNAs might be more specific in HCC, while NRAV and CMB9-22P13.1 were 13 BioMed Research International rarely reported as an oncogene in cancers. Similar with RHPN1-AS1, MAPKAPK5-AS1 was frequently reported to act as tumor-promoting lncRNAs in multiple cancers like thyroid cancer, colorectal cancer, glioma, lung cancer, and HCC [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Among these lncRNAs, RHPN1-AS1 was reported to act as an oncogene in multiple human cancers, including nonsmall cell lung cancer [19], uveal melanoma [20], and breast cancer [21]. LINC01134 and MKLN1-AS were found to promote HCC progression or metastasis by previous studies [24][25][26][27][28], suggesting that the two lncRNAs might be more specific in HCC, while NRAV and CMB9-22P13.1 were 13 BioMed Research International rarely reported as an oncogene in cancers. Similar with RHPN1-AS1, MAPKAPK5-AS1 was frequently reported to act as tumor-promoting lncRNAs in multiple cancers like thyroid cancer, colorectal cancer, glioma, lung cancer, and HCC [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…MKLN1-AS was overexpressed and contributed to poor prognosis in HCC patients ( Guo et al, 2021 ). In addition, MKLN1-AS increases HDGF expression by functioning as a molecular sponge for miR-654-3p, resulting in a cancer-promoting effect during the HCC process ( Gao et al, 2020 ). MIR4435-2HG can promote immunometabolic activities of primary myeloid dendritic cells by targeted epigenetic modifications of a part of mTOR signaling pathway ( Hartana et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DUXAP8 promotes the growth and proliferation of HCC cell lines by suppressing Krüppel-like factor 2 (KLF2) expression ( Jiang, et al, 2019 ). ( Gao, et al, 2020 ) revealed that MKLN1-AS promoted HCC progression by acting on miR-654-3p, and down-regulation of MKLN1-AS inhibits the aggressive phenotype of HCC cells. RHPN1-AS1 enhances the proliferation and invasion process of HCC cells by targeting miR-7-5p ( Song, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%